Implikasi Hukum Perubahan Kedua Undang-Undang Informasi dan Transaksi Elektronik: Menyeimbangkan Kebebasan Berpendapat dan Partisipasi Publik dalam Demokrasi Digital - Zainal Arifin; Zico Junius Fernando; Emi Puasa Handayani (Jurnal Litigasi)
This study examines the legal implications of the second amendment to the Electronic Information and Transactions Law (UU ITE) through Law No. 1 of 2024 on public participation in cyberspace, particularly in the context of general elections (PEMILU). Over time, the UU ITE has often been regarded as ambiguous and repressive, potentially hindering freedom of expression. Provisions such as Articles 27A and 27B, while intended to replace previously criticized "rubber articles," continue to face criticism for perpetuating a chilling effect. This situation raises concerns about the declining quality of public participation in digital democracy processes. However, studies on the impact of the second amendment to the UU ITE on freedom of expression in the 2024 elections, as well as comparative analyses of more proportional international regulations, remain limited, necessitating further research. This study employs a descriptive qualitative approach to analyze the implications of the amendments to the UU ITE on freedom of expression and public participation in elections. The findings reveal that the unclear regulations in the UU ITE may lead to legal uncertainty, marginalize certain groups, and create inequality in access to information. Reforming the UU ITE is essential to ensure that the regulations align with democratic principles, protect freedom of expression, and promote inclusive public participation. The novelty of this study lies in its specific analysis of the revised provisions in Law No. 1 of 2024 and their impact on freedom of expression in the 2024 elections, incorporating a global comparative approach to propose a more just and...